CO2 Emission in Green Buildings: An Analysis of Energy Efficiency and Financial Viability in Jordan - Sammour, George; Shahateet, Mohammed Issa (International Journal of Energy Economics and Policy, 2024)
This paper aims to use photovoltaics as a case study of a green building in Jordan to provide electric power, boost the power provided by the national grid, and enhance energy policies to reduce CO2 emissions. The photovoltaic PV panels are used to provide nearly 7.4 kW of electricity power for the lighting. The study uses Renewable Energy and Energy Efficiency Technology Screen (RETScreen) computer software to achieve this aim. Three different aspects were subjected to the analysis: Firstly, the proposed case power system; secondly, emission analysis; and finally, financial analysis. The worksheet of the analysis of emission reduction is used to estimate the emission of CO2 in the proposed project. The study findings reveal that the GHG emission factor in tCO2/MWh equals 0.924, while the net annual GHG emission reduction in tCO2 is 8,367.4, which is equivalent to the consumption of 19,459 barrels of crude oil.